(untitled) (Herald of Journalism, 2016)
The article illuminates the statements of research journalism. Providing the examples of the works in the archives of Kazakhstan, Russia and Belarus, the problems, perspectives and necessity of studying the past by journalists and historians is illustrated. The interest towards the topic of state structures is pointed out.